Analisis Pengaruh Kecepatan Angin Terhadap Penyebaran Spora Dan Keparahan Penyakit Bercak Daun (Cercospora sojina) Pada Tanaman Edamame (Glycine max L.) - M.ilham Pasaribu; Guntoro (Lembaga Teewan Journal Solutions, 2026)
Leaf spot disease caused by Cercospora sojina is one of the major constraints to edamame (Glycine max L.) production. The epidemiology of this disease is closely associated with environmental factors, particularly wind speed, which influences spore dispersal and conidial abundance. This study aimed to analyze the effects of wind speed and conidial abundance on the severity of leaf spot disease in edamame. The research was conducted at the Experimental Farm of the Indonesian Institute of Palm Oil Technology (ITSI), Deli Serdang, North Sumatra, from April to June 2026. Wind speed, conidial abundance, and disease severity were observed and analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results showed that wind speed had a positive but relatively weak relationship with disease severity (r = 0.357; R² = 12.7%), whereas conidial abundance exhibited a strong positive relationship (r = 0.748; R² = 56.0%). Multiple regression analysis indicated that both variables simultaneously explained 59.0% of the variation in disease severity, with conidial abundance identified as the dominant factor. These findings demonstrate that conidial abundance plays a more important role than wind speed in the epidemiology of C. sojina leaf spot disease and provides useful information for improving disease monitoring and environmentally based management strategies in edamame cultivation.